Comparison of Outcomes in Lateral Sphincterotomy and Anal Advancement Flap in the Treatment of Chronic Anal Fissure - Hamza Tahir, Rabia Ahmad, Ali Akbar Subhani, Muhammad Jarar, Babar Minhas, Kamran Chodhary (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: For the comparison of outcomes in lateral sphincterotomy and anal advancement flap in the treatment of chronic anal fissure. Study Design: Randomized clinical trial Place and Duration of Study: Jinnah Hospital, Lahore from 1st April 2021 to 31st March 2022. Methodology: One hundred patients of age >15 years were enrolled. Patients were defined as preoperative according to the definition of chronic anal fissure. Patients were divided into two groups, 50 patients in each group. The first group underwent lateral sphincterotomy while the second group was operated through anal advanced flap procedure. The wound infection was observed on day third as a post-operative protocol. Anal incontinence was determined post 3 months of surgery by any procedure conducted. Vaizey-scoring was used for determining anal incontinence. Results: The mean age of the patients was 39.5±4.7 years in lateral sphincterotomy group while it was 38.9±5.1 year in anal advanced flap. The highest number of cases was reported between the age group of 15-35 years within both operative procedures. The fissure healing was observed in 88% of lateral sphincterotomy group which lower than the observed values of 96% in anal advanced flap group. The follow up data also showed an increased case of infection and anal incontinence in lateral sphincterotomy group when compared with anal advanced flap cases. Conclusion: Anal advancement flap surgical method is considerably a better treatment method for the treatment of anal fissures. Key words: Pharmacological interventions, Anal fissures, Constipation, Chronic, Sphincterotomy